Results-based management in practice: Lessons learnt and policy recommendations from the implementation of RBM in European fisheries outside Europe. (May 2022) - Arias, Juliana; Laksá, Unn; Fonseca, Benvido D'Oliveira; Diallo, Mamadou; Brahim, Khallahi; Rodríguez, Alexandre; Doblado, Sonia Martin; Galvão, Juliana Antunes; Viðarsson, Jónas R.; Friðriksdóttir, Ragnhildur
Abstract: This paper summarizes the lessons learnt from the implementation of a practical approach to Results-based Management (RBM) within the EU H2020 FarFish project, where RBM is conceptualized as a contract situation. From these lessons a set of policy recommendations for the improvement of the fisheries management through the adoption of RBM for EU vessels fishing in international- and Sustainable Fisheries Partnership Agreements (SFPA) waters were put forward. The policy recommendations are based on key project outputs and additional semi-structured interviews on the experiences of project partners. This exercise revealed advancements and shortcomings for the broader implementation of a more participatory, inclusive, and responsive approach to fisheries governance. Meaningful and effective participation was a pivotal factor for the success of the process. Absence of relevant bodies, sectors and fleet segments proved detrimental throughout all cases. The importance of scoping, goal setting and timing of the actions, as well as managing realistic expectations within the RBM, were highlighted. Data availability and accountability was pivotal, as in cases were cooperation succeeded, data was made available, and knowledge was expanded and enriched. The implementation of this approach to RBM showed great potential when extended to other aspects of fisheries' management, fishing categories and fleets. This structured approach to RBM provides a promising alternative to current fisheries management systems across the world.